Analisis Pertanggungjawaban Pidana terhadap Penganiayaan Ringan : (Studi Putusan Nomor 1748/Pid.B/2023/PN Lbp) - Jahtra Solin; Dani Sintara (Jurnal Hukum dan Sosial Politik, 2024)
Abuse is a crime against the body (physical). The word abuse as stated in the Big Indonesian Dictionary (KBBI) is arbitrary treatment (torture, oppression, and so on). From this definition, it is expanded again in terms of meaning, namely concerning "inner" or "feelings". The purpose of this study is to find out how criminal responsibility is imposed on perpetrators of abuse that causes minor injuries as regulated in Indonesian criminal law regulations The type of research used in this study is empirical legal research, namely legal research conducted by directly examining or secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The data obtained from this study were analyzed using qualitative analysis, namely describing the existing realities based on the results of the study by systematically describing them to obtain clarity and facilitate discussion. Based on the results of the study, criminal responsibility for perpetrators of minor abuse that causes minor injuries in Indonesian criminal law is a combination of the application of basic principles of criminal law such as the principles of legality, proportionality, and intent, as well as flexibility in determining appropriate sanctions based on mitigating or aggravating factors. Ordinary assault is regulated in Article 351 of the Criminal Code, while minor assault is regulated in Article 352 of the Criminal Code. Premeditated and serious assault have stricter provisions, with heavier sanctions for the perpetrators. Based on the results of the research that has been conducted, it can be concluded that: Criminal liability for perpetrators of assault that causes minor injuries is regulated in the Criminal Code (KUHP), especially Article 352 of the Criminal Code. The judge's considerations in decision number 1748/Pid.B/2023/PN Lbp.